Mapping protein-protein interactions in the apoptosis pathway. - Triani, Renata. (2010)
Apoptosis or programmed cell death is a crucial process in almost all living organisms. It is important for evolution, homeostatic maintenance and proper development of an organism. Many apoptosis-related studies had been conducted using genetic, cellular, systematical, and structural biological approaches. These studies have resulted in the identification of hundreds of proteins known to regulate the apoptosis process and hence increased the understanding of its mechanism. My project focuses on modeling the three-dimensional structures of protein complexes that are formed during apoptosis in Drosophila melanogaster. By building three-dimensional model of apoptotic proteins, we can identify what proteins interact, how they interact and what residues are important for these interactions. To achieve this, Drosophila melanogaster apoptotic proteins were structurally annotated for known protein binding surfaces using the interface library developed by Dr. Minh Ngoc Nguyen. Proteins with complementary interfaces were matched structurally to model the interaction between proteins in three-dimensions and several assessments were performed to refine the models of complex structure. For the final assessment, a statistical potential was performed to define the true interactions. In this project, 38 new interactions between 27 proteins in the apoptosis pathway of Drosophila melanogaster were identified. These candidate complexes will then be validated experimentally.